Enforcement Efficiency of the Act on Minors' Rights Protection - DUGARON, Yelena Tsibikovna; MADAGAYEVA, Tatyana Fedorovna; SHODONOVA, Maria Eduardovna (Journal of Advanced Research in Law and Economics, 2016)
This paper deals with some issues concerning assessment of enforcement efficiency of the Act on minors' rights protection in the Russian Federation. It investigates the dynamics of the Russian legislation on children's rights protection, and gives analysis of the public authorities' performance in implementing the Act on children's rights (the case of the Republic of Buryatia). In particular, the authors give characteristics of the public bodies engaged in protecting the rights of children in difficult life situations, including children without parental support and those who committed crimes and antisocial actions. The paper demonstrates the practices of Ombudsman for Children in the Republic of Buryatia. It reveals the main probable causes of low efficiency in protection of minors' rights, i.e. insufficient systematicity of the legislation, ineffective interdepartmental interaction, poor quality of the staff employed with the public bodies and establishments for the minors' rights protection, and lack of preventive measures in the work of corresponding public bodies. Another focus of the research has been on the Russian Federal Act on mediative forms of social conflict settlement within the children's rights protection mechanism. Prospects for practical use of the mediative technologies have been revealed. The paper shows a demand for further discussions of the existing legislation towards feasibility of specialized mediation that will ensure higher efficiency in the protection of children's rights.